If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -89 = 6x + 2x + -9 Reorder the terms: -89 = -9 + 6x + 2x Combine like terms: 6x + 2x = 8x -89 = -9 + 8x Solving -89 = -9 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -89 + -8x = -9 + 8x + -8x Combine like terms: 8x + -8x = 0 -89 + -8x = -9 + 0 -89 + -8x = -9 Add '89' to each side of the equation. -89 + 89 + -8x = -9 + 89 Combine like terms: -89 + 89 = 0 0 + -8x = -9 + 89 -8x = -9 + 89 Combine like terms: -9 + 89 = 80 -8x = 80 Divide each side by '-8'. x = -10 Simplifying x = -10
| 2/5+2x=-28/5 | | 12-12z=-9-10 | | p-36=44/9(h-6) | | 18u^6-8u^4/2u^3 | | h=-16t^2+64t+720 | | Z=12 | | 25+24z=25+25z | | 60x-0.2x^2=p(x) | | 45+9y=90 | | -18=-3/5w | | 2v=-14/9 | | 6.5/3X+5=111/2 | | -3.9+m=-3.9 | | 2v=14/9 | | z^2-iz+12=0 | | 60-2P=-20+4P | | -7x=-3x-12 | | 3+7x=12-12x | | 14d+9=6d+25 | | 6(x-3)=-4.2 | | -2(-8u+3)-7u=5(u-1)-7 | | 8(a+1)=21.6 | | -43-3x=6-9x | | 33.7=9c-5 | | 3e-5=19.9 | | Y-23-37Y=3 | | p-18=18(h-6) | | 5x-14=16x | | p-18=23/3(h-6) | | 1x+34=26 | | 2x^2-12x+68=100 | | p=23/6h+18 |